Cloud Model for Purchase Management in Health Sector of Peru based on IoT and Blockchain - Celiz, Rodrigo Cubas (2019)
Purchase management of medical supplies is a critical and important process that affects the services provision quality. Nonetheless, it is facing a growing pressure to provide visibility and traceability of the purchase, to reduce fraud, to improve flexibility and to ensure communication between everyone involved. Currently, private health institutions in Peru choose to implant different software products within the same company with restricted visibility access to other concerned parties and based on information from a single source. A new alternative is Blockchain technology, since it provides a single source of shared truth to all participants and ensures that the information cannot be altered, thus offering high levels of transparency that, together with IoT technology, creates not only visibility about where things are, but also traceability, showing the current state of things.